ARTIGAS, M., Ciencia y Religión. Conceptos fundamentales - Sequeiros, L. (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
(EUNSA, Pamplona, 2007). 422 pp. ISBN: 978-84-313-2490-2.